Mediasi Kepuasan Pasien pada Dimensi Kualitas Pelayanan Assurance terhadap Word of Mouth - Harry Ansis; Hasyim Hasyim; Andry Andry (Jurnal Health Sains, 2021)
Word of Mouth is a natural conversation between individuals about information of a product that is considered to have more influence than advertising and formal marketing. The quality of service is an important determinant of customer satisfaction and Word of Mouth performed by customers during the use of the service. The lack of interest in the patient or their family to tell others about an experience while being treated at X Hospital Jakarta, occurred because of the low quality of service which resulted in a sense of dissatisfaction. The purpose of this study was to determine the effect of Service Quality Dimensions on Word of Mouth mediated by Patient Satisfaction. The research method used is quantitative research with the type of Causality Explanation Research. The sample in this study were 200 patients who had been treated at X Hospital Jakarta. The technique used is Stratified Proportional Random Sampling. The results of the research is that the Dimensions of Service Quality both directly and indirectly with Patient Satisfaction as a Mediating Variable are proven to affect the level of a patient's Word of Mouth. The research finding is that the existence of Patient Satisfaction as a Mediating Variable, the influence of one of the Service Quality Dimensions, namely Assurance, has a greater impact on the patient's Word of Mouth. This means that the patient's Word of Mouth cannot be improved optimally by relying on Assurance alone, but it is necessary to establish patient satisfaction